Business Ethics in the Qur'an: A Deontological and Maqasidi Analysis Based on Tafsir al-Tahrir wa al-Tanwir and Tafsir al-Munir - Fadillah, Muhammad Yuga; Ahmad, Khadher bin (UIN Sunan Gunung Djati Bandung, 2025)
This study examines business ethics in the context of the Quran, as interpreted in Tafsir Al-Tahrir Wa Al-Tanwir and Tafsir Al-Munir, employing both deontological and maqāṣid approaches. It analyzes four Quranic verses related to honesty, trustworthiness, responsibility, and professionalism. The research compares interpretations by Ibn Ashur and Wahbah, highlighting differences in maqāṣid and fiqh perspectives. It argues that these ethics are absolute obligations in Islam, aligning with Kantian deontology, which aims to eliminate unethical business practices and promote social and economic justice for the benefit of both this world and the hereafter.